PENGELOLAAN ALOKASI DANA DESA KECAMATAN BANYUKE HULU KABUPATEN LANDAK (STUDI KASUS DI DESA UNTANG) - B21110017, Supriyanto (Jurnal Pembangunan dan Pemerataan, 2016)
The objective of this study was to produce a change in the management of Village Allocation Fund (VAF), which includes the planning, implementation and monitoring. The study results showed that 40% of the total allocation of Village Fund is in compliance with statutes and regulations. The funds ware mostly used to finance allowances/intensive village apparatus and BPD. Meanwhile 60% of the total funds were used for physical development or rural infrastructure such as roads of Rabat Concrete and economy business potency of savings and loans rural communities. This study also indicated that physical participation of rural communities both in planning, implementation, and monitoring of activities originating from the Village Allocation is less maximal. Keywords: Village Fund Allocation management, planning, implementation, andÂ  monitoring.